2013
DOI: 10.1093/infdis/jit269
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Specific Borrelial Antigens Appear to Be Upregulated in American but Not European Patients With Lyme Arthritis, a Late Manifestation of Lyme Borreliosis

Abstract: Borrelia burgdorferi (Bb) sensu lato, the etiologic agent of Lyme borreliosis, adapts to distinct environments in the mammalian host and the tick vector by differential gene expression. As a result, infected mice are not exposed to and rarely make antibodies to the set of antigens that are preferentially expressed in the tick, including outer surface protein A (OspA), Borrelia iron and copper-binding protein A (BicA), and OspD. Surprisingly, however, antibodies to OspA and BicA have been noted in American pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…In addition to the brain of two treated animals, rare morphologically intact spirochetes immunoreactive to OspA were observed in the heart of one treated animal (IK14). Increased OspA serum titers have been reported in American patients with Lyme arthritis and indicate differential gene expression of B. burgdorferi dependent on tissue localization 46, 47. Furthermore, experimental studies in mice have shown enhanced OspA expression in host-adapted spirochetes during inflammation 48 and ospA transcription was evident posttreatment in both murine studies and our prior study in macaques 13, 49.…”
Section: Discussionsupporting
confidence: 60%
“…In addition to the brain of two treated animals, rare morphologically intact spirochetes immunoreactive to OspA were observed in the heart of one treated animal (IK14). Increased OspA serum titers have been reported in American patients with Lyme arthritis and indicate differential gene expression of B. burgdorferi dependent on tissue localization 46, 47. Furthermore, experimental studies in mice have shown enhanced OspA expression in host-adapted spirochetes during inflammation 48 and ospA transcription was evident posttreatment in both murine studies and our prior study in macaques 13, 49.…”
Section: Discussionsupporting
confidence: 60%
“…This proportion is similar to that documented in southwest Virginia, where 6% of healthy, non‐vaccinated horses were seropositive for OspA antibodies . The magnitude of OspA antibody response in American human patients with Lyme arthritis has been directly correlated with more severe and prolonged disease . In our study, more horses with positive CSF OspA results or positive CSF : serum OspA ratios had a final diagnosis of another neurologic disease than neuroborreliosis.…”
Section: Discussionsupporting
confidence: 87%
“…That we are seeing it induced after doxycycline treatment is of interest and may parallel what we see with OspA (below). OspD is an outer membrane protein, located on plasmid lp38, which is known to be antigenic (Li et al, 2013) and expressed more highly in ticks than in the mammalian host (Li et al, 2007). BBA62 was described in 1997 as a 6.6 kD lipoprotein that did not appear to induce antibodies by animals needle-inoculated with B. burgdorferi (Lahdenne et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, ospA, ospB , and ospD appear to be regulated by the stress-response regulator bosR (Wang et al, 2013). These gene products are possible markers of dormancy, given their expression in ticks and in late Lyme arthritis (Li et al, 2013). In our study, bosR was shown to be up-regulated 0.325-fold following treatment and rpoS was up 0.386-fold; however, the p -values indicate that these were not significant perturbations.…”
Section: Discussionmentioning
confidence: 99%